Penser l’altérité avec Lost : Foucault, Lacan et la médiation du regard - Louis-Paul Willis (TV Series, 2016)
Among the numerous references to philosophy that permeate its narrative universe, Lost seems to be predominantly traversed by Foucauldian themes, mostly related to articulations of looking dynamics and surveillance. Themes related to panopticism and discipline constitute notable underpinnings for the series’ plot, as several previous analyses have pertinently demonstrated. This article proposes an examination of the spectatorial repercussions related to this facet of Lost, most importantly by establishing ties between the panoptic gaze and the gaze in its psychoanalytic conception, elaborated by Jacques Lacan. By examining both these concepts of a gaze deployed around the position of the Other, this article focuses on the series’ exploration of subjectivity in the era of panopticism. By exploring the importance and narrative deployment of these notions of the gaze within Lost, it is suggested that the series articulates a certain radicality around the notion of Otherness, as well as its expression through the televisual mediation of the gaze.